An analysis the impact of subjective Well-being and emotional intelligence On meditators: Examining the Impact of Meditation on Subjective Well-being and Emotional Intelligence (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Meditation is a type of mental exercise that aims to increase a person's capacity for selfawareness.A new state of awareness is induced, resulting in positive outcomes for all of humanity.Meditation is a cornerstone of developing emotional intelligence and overall health. In examining theeffect of meditation on EI subjective well-being among mediators regardless of age, gender, etc ofmeditation they practice. This study is systematically and scientifically organized. The validity ofresearch is determined by a systematic approach to data gathering and analysis in a methodical manner.It has made an general usage of both primary secondary data. It describes EI subjective well-beingof the mediators in Indore Madhya Pradesh and hence the study is descriptive in nature. So, thisinvestigates usages sampling technique for collecting data.